An Unusual Occupational Injury: Radial Crack Related to Tooth Extraction - Torul, Damla; Omezli, Mehmet Melih; Ayranci, Ferhat; Altay, Damla Aydin (Odovtos - International Journal of Dental Sciences, 2020)
Dentists are vulnerable to occupational injuries associated with dental procedures, and to their work environment. Lack of appropriate and safe working conditions can put dental professionals at risk of injuries, the majority of which are musculoskeletal, especially in the wrist. This report presents a case of a radial crack in the wrist of a dental student which occurred as a complication of a tooth extraction procedure. Also, emphasises the need for education about workplace risks and hazards, starting at the undergraduate level, to promote prevention of occupational injuries.